Compound and application thereof, non-aqueous electrolyte and battery
By using compounds containing cyclic carbonate groups and siloxane groups as additives in the battery, the problems of increasing impedance and insufficient film formation stability in the prior art are solved, and the high-temperature performance and impedance optimization of the battery are improved.
Patent Information
- Application Number
- CN202311384186.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
AI Technical Summary
The film-forming additives of the existing electrolyte have problems of insufficient enlarging the battery impedance and film-forming stability, and it is difficult to take into account the high-temperature performance and impedance of the battery.
A compound containing a cyclic carbonate group and a silicone group is provided as an additive to the nonaqueous electrolyte. These groups participate in the formation of a passivation film on the surface of the electrode material during the battery formation process, thereby improving the stability of the passivation film and the uniformity of the film thickness.
It effectively improves the high-temperature performance of the battery, reduces the film formation impedance, and the formed passivation film has good ion permeability, avoiding the increase in the battery impedance.
Smart Images

Figure CN119874757A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a compound and application thereof, a non-aqueous electrolyte and a battery. Background Art
[0002] Metal lithium batteries have become one of the most promising next-generation energy storage battery systems due to their extremely high theoretical energy density. However, the growth of dendrites and low coulombic efficiency during the cycle process have greatly hindered the practical application of metal lithium batteries. When metal lithium batteries use transition metal oxides as positive electrode materials, carbonate solvents are an indispensable component of the electrolyte. Finding stable carbonate solvents that can form a stable SEI on the surface of metal lithium anodes is an important way to achieve stable cycling of metal lithium batteries.
[0003] The effects of different cyclic carbonate solvents on the cycling stability of metal lithium batteries were determined in the full battery system. These cyclic carbonate solvents actively participate in the formation of SEI at the anode interface. The substitution of fluorine atoms in cyclic carbonates can greatly improve the stability of metal lithium anodes.
[0004] In order to improve the performance of lithium-ion batteries, many researchers have added different negative electrode film-forming agents to the electrolyte, such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), diethylene sulfate (DTD) and other additives to improve the quality of the SEI film, thereby improving the performance of the battery. Although the existing film-forming additives can improve the high-temperature performance of the battery to a certain extent, they still cannot meet the needs of the market. At the same time, the film-forming additives will increase the impedance of the battery to a certain extent. How to develop an additive that can take into account both the high-temperature performance and impedance problems of the battery is an urgent problem to be solved. Summary of the invention
[0005] Aiming at the problems that the existing film-forming additives of electrolytes increase battery impedance and have insufficient film-forming stability, the present invention provides a compound and application thereof, a non-aqueous electrolyte and a battery.
[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0007] In one aspect, the present invention provides a compound selected from the compounds shown in structural formula 1:
[0008]
[0009] wherein x is an integer of 0-3, y is an integer of 0-3, 1≤x+y, a is an integer of 0-4, b is an integer of 0-4, c is an integer of 0-4, 1≤a+b+c, R1, R2 and R3 are each independently selected from an alkylene group having 1-4 carbon atoms, R4 and R5 are each independently selected from hydrogen or an alkyl group having 1-6 carbon atoms; R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 and R 14 Each is independently selected from an alkyl group having 1 to 6 carbon atoms.
[0010] Optional, x+y≤3, a+b+c≤8.
[0011] Optionally, the compound represented by structural formula 1 is selected from one or more of the following compounds:
[0012]
[0013]
[0014] In another aspect, the present invention provides use of the compound as described above as an additive for a non-aqueous electrolyte.
[0015] In yet another aspect, the present invention provides a non-aqueous electrolyte comprising a non-aqueous organic solvent, an electrolyte salt and a first additive, wherein the first additive comprises the compound as described above.
[0016] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the content of the compound represented by structural formula 1 is 0.05-10%.
[0017] Optionally, the electrolyte salt is selected from at least one of lithium salt, sodium salt, potassium salt, magnesium salt, zinc salt and aluminum salt.
[0018] Optionally, the non-aqueous electrolyte further includes a second additive, and the second additive includes at least one of a cyclic sulfate ester compound, a sultone compound, a cyclic carbonate compound, a phosphate ester compound, a borate ester compound and a nitrile compound.
[0019] Optionally, the cyclic sulfate ester compound is selected from vinyl sulfate, 4-methylvinyl sulfate, propylene sulfate, At least one of;
[0020] The sultone compound is selected from 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, At least one of;
[0021] The cyclic carbonate compound is selected from vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate or structure
[0022] At least one of the compounds shown in Formula 2:
[0023]
[0024] In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group;
[0025] The phosphate compound is selected from at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in structural formula 3:
[0026]
[0027] In the structural formula 3, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group;
[0028] The borate compound is selected from at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate;
[0029] The nitrile compound is selected from at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
[0030] Optionally, the non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent and a sulfone solvent.
[0031] In another aspect, the present invention provides a battery comprising a positive electrode, a negative electrode and the non-aqueous electrolyte as described above.
[0032] According to the compound provided by the present invention, a new compound used as a film-forming additive for battery non-aqueous electrolyte is developed, and a new preparation method of the new compound is also provided. The compound shown in the structural formula 1 contains both a cyclic carbonate group and a siloxane group. During the battery formation process, the cyclic carbonate group and the siloxane group jointly participate in the formation of a passivation film on the surface of the electrode material. The cyclic carbonate group decomposes to obtain the main component of the passivation film containing lithium carbonate and other lithium-containing compounds, and the siloxane group has a cross-linking effect, which further improves the stability of the passivation film and the uniformity of the film thickness, especially the improvement of the stability under high temperature conditions. The formed passivation film has good ion permeability, which avoids the increase of the battery impedance. DETAILED DESCRIPTION
[0033] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] An embodiment of the present invention provides a compound selected from the compound shown in structural formula 1:
[0035]
[0036] wherein x is an integer of 0-3, y is an integer of 0-3, 1≤x+y, a is an integer of 0-4, b is an integer of 0-4, c is an integer of 0-4, 1≤a+b+c, R1, R2 and R3 are each independently selected from an alkylene group having 1-4 carbon atoms, R4 and R5 are each independently selected from hydrogen or an alkyl group having 1-6 carbon atoms; R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 and R 14 Each is independently selected from an alkyl group having 1 to 6 carbon atoms.
[0037] The compound shown in the structural formula 1 contains both cyclic carbonate groups and siloxane groups. During the battery formation process, the cyclic carbonate groups and the siloxane groups jointly participate in the formation of a passivation film on the surface of the electrode material. The cyclic carbonate groups decompose to obtain the main component of the passivation film containing lithium carbonate and other lithium-containing compounds, and the siloxane groups have a cross-linking effect, which further improves the stability of the passivation film and the uniformity of the film thickness, especially the stability under high temperature conditions. The formed passivation film has good ion permeability, which avoids the increase of the battery impedance.
[0038] In some embodiments, x+y≤3, a+b+c≤8.
[0039] The x+y value is related to the amount of cyclic carbonate contained in the compound shown in Structural Formula 1, and the a+b+c value is related to the amount of siloxane groups contained in the compound shown in Structural Formula 1. When the x+y value or the a+b+c value is too large, the viscosity of the compound shown in Structural Formula 1 will increase, affecting its dispersibility and film-forming properties in the non-aqueous electrolyte.
[0040] In some embodiments, the compound represented by structural formula 1 is selected from one or more of the following compounds:
[0041]
[0042] It should be noted that the above are only examples of some compounds provided by the present invention and do not represent limitations of the present invention.
[0043] A person skilled in the art, knowing the structural formula of the compound shown in Structural Formula 1, can know the preparation method of the above compound according to the common knowledge in the field of chemical synthesis.
[0044] One embodiment of the present invention provides a method for preparing the compound represented by structural formula 1, comprising the following steps:
[0045] Transesterify the polyol and the carbonate to generate a monocyclic carbonate and / or a polycyclic carbonate with unreacted hydroxyl groups;
[0046] The purified monocyclic carbonate and / or polycyclic carbonate with unreacted hydroxyl groups is subjected to substitution reaction with trialkylchlorosilane under alkaline conditions to generate a compound shown in structural formula 1.
[0047] As an example of the present invention:
[0048] Compound 1 can be prepared by the following method:
[0049] Glycerol is reacted with an equivalent amount of carbonate to synthesize glycerol cyclic carbonate, which is purified by reduced pressure distillation, and then the purified glycerol cyclic carbonate is reacted with trimethylchlorosilane under alkaline conditions to form glycerol cyclic carbonate trimethylsilyl ether, thereby obtaining compound 1.
[0050] Compound 3 can be prepared by the following method:
[0051] Butanethrol is reacted with an equivalent amount of carbonate to synthesize butanethrol cyclic carbonate, which is purified by recrystallization. The purified butanethrol cyclic carbonate is then reacted with trimethylchlorosilane under alkaline conditions to generate butanethrol cyclic carbonate trimethylsilyl ether, thereby obtaining compound 3.
[0052] Compound 13 can be prepared by the following method:
[0053] Glycerol is reacted with an equivalent amount of carbonate to synthesize glycerol cyclic carbonate, which is purified by reduced pressure distillation. The purified glycerol cyclic carbonate is then reacted with triethylsilyl chloride under alkaline conditions to generate glycerol cyclic carbonate triethylsilyl ether, thereby obtaining compound 13.
[0054] Compound 14 can be prepared by the following method:
[0055] Xylitol was reacted with 2 equivalents of carbonate to synthesize xylitol bicyclic carbonate, which was purified by recrystallization. The purified xylitol bicyclic carbonate was then reacted with triethylchlorosilane under alkaline conditions to generate xylitol bicyclic carbonate triethylsilyl ether, thereby obtaining compound 14.
[0056] Another embodiment of the present invention provides use of the compound as described above as an additive for a non-aqueous electrolyte.
[0057] Another embodiment of the present invention provides a non-aqueous electrolyte solution including a non-aqueous organic solvent, an electrolyte salt and a first additive, wherein the first additive includes the compound as described above.
[0058] Since the compound as described above is used as the first additive of the non-aqueous electrolyte, the film formation stability on the electrode surface during the non-aqueous electrolyte formation stage can be effectively improved, the film formation impedance can be reduced, and thus the high temperature performance of the battery can be effectively improved.
[0059] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the content of the compound represented by structural formula 1 is 0.05-10%.
[0060] In a specific embodiment, based on the total mass of the non-aqueous electrolyte as 100%, the content of the compound shown in structural formula 1 can be 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5% or 10%.
[0061] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the content of the compound represented by structural formula 1 is 0.1% to 5%.
[0062] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the content of the compound represented by structural formula 1 is 0.1% to 2%.
[0063] When the content of the compound shown in Structural Formula 1 in the non-aqueous electrolyte is within the above range, the stability of the film formed on the electrode surface can be effectively maintained and the battery performance can be improved. If the content of the compound shown in Structural Formula 1 is too little, it is difficult to have a significant improvement effect on the performance of the battery; if the content of the compound shown in Structural Formula 1 is too much, it may affect the functions of other substances in the electrolyte due to its excessive decomposition products.
[0064] In some embodiments, the electrolyte salt is selected from at least one of lithium salts, sodium salts, potassium salts, magnesium salts, zinc salts, and aluminum salts.
[0065] In a preferred embodiment, the electrolyte salt is selected from lithium salt or sodium salt.
[0066] The alkali metal ions formed by the dissociation of the electrolyte salt in the non-aqueous electrolyte are embedded and deintercalated between the positive and negative electrodes to complete the charge and discharge cycle. The concentration of the electrolyte salt directly affects the transfer speed of the alkali metal ions, and the transfer speed of the alkali metal ions affects the potential change of the negative electrode. During the rapid charging process of the battery, it is necessary to increase the movement speed of the alkali metal ions as much as possible to prevent the negative electrode potential from dropping too fast, resulting in the formation of lithium dendrites, which poses a safety hazard to the battery, and at the same time prevent the battery's cycle capacity from decaying too quickly. When the content of the electrolyte salt is too low, the embedding and extraction efficiency of the alkali metal ions between the positive and negative electrodes will be reduced, and the demand for fast charging of the battery cannot be met; when the content of the electrolyte salt is too high, the viscosity of the non-aqueous electrolyte will increase, which is also not conducive to the improvement of the embedding and extraction efficiency of the alkali metal ions, and increases the internal resistance of the battery.
[0067] In a specific embodiment, the concentration of the lithium salt is 0.1mol / L-8mol / L. In a preferred embodiment, the concentration of the lithium salt is 0.5mol / L-2.5mol / L. Specifically, the concentration of the electrolyte salt can be 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L.
[0068] In a preferred embodiment, the lithium salt is selected from LiPF6, LiBOB, LiDFOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO2F)2, LiClO4, LiAlCl4, LiCF3SO3, Li2B 10 Cl 10 , at least one of a lithium salt of a lower aliphatic carboxylate.
[0069] In a specific embodiment, the concentration of the sodium salt is 0.1mol / L-2mol / L. In a preferred embodiment, the concentration of the sodium salt is 0.4mol / L-1.5mol / L. Specifically, the concentration of the sodium salt can be 0.1mol / L, 0.4mol / L, 0.5mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 2mol / L.
[0070] In a specific embodiment, the sodium salt is selected from at least one of sodium perchlorate (NaClO4), sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium bis(trifluoromethylsulfonyl)imide (NaFSI), sodium trifluoromethylsulfonate (NaOTf), and sodium bis(trifluoromethylsulfonyl)imide (NaTFSI).
[0071] In some embodiments, the non-aqueous electrolyte further includes a second additive, and the second additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a borate compound, and a nitrile compound.
[0072] Preferably, based on the total mass of the non-aqueous electrolyte being 100%, the content of the second additive is 0.01% to 10%.
[0073] In some embodiments, the cyclic sulfate ester compound is selected from vinyl sulfate, 4-methylvinyl sulfate, propylene sulfate, At least one of;
[0074] The sultone compound is selected from 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, At least one of;
[0075] The cyclic carbonate compound is selected from at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate or the compound shown in Structural Formula 2:
[0076]
[0077] In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group;
[0078] More preferably, the compound represented by structural formula 2 includes at least one of the following compounds 2-1 to 2-6:
[0079]
[0080] Compound 2-4 Compound 2-5 Compound 2-6;
[0081] The phosphate compound is selected from at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in structural formula 3:
[0082]
[0083] In the structural formula 3, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group;
[0084] In a preferred embodiment, the phosphate compound shown in the structural formula 2 may be at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate;
[0085] The borate compound is selected from at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate;
[0086] The nitrile compound is selected from at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
[0087] In other embodiments, the second additive may also include other additives that can improve battery performance: for example, additives that enhance battery safety performance, such as flame retardant additives such as fluorophosphates and cyclophosphazenes, or overcharge prevention additives such as tert-amylbenzene and tert-butylbenzene.
[0088] It should be noted that, unless otherwise specified, in general, the content of any one of the optional substances in the second additive in the non-aqueous electrolyte is less than 10%, preferably, the content is 0.01-5%, and more preferably, the content is 0.1% to 2%. Specifically, the content of any one of the optional substances in the second additive can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10%.
[0089] In some embodiments, the second additive includes fluoroethylene carbonate, and based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the fluoroethylene carbonate is 0.01% to 30%.
[0090] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the non-aqueous organic solvent is 65% to 90%.
[0091] Specifically, based on the total mass of the non-aqueous electrolyte as 100%, the mass content of the non-aqueous organic solvent can be 65%, 68%, 71%, 74%, 76%, 78%, 79%, 80%, 81.5%, 82%, 84%, 85%, 86%, 87%, 89%, or 90%.
[0092] In some embodiments, the non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, and a carboxylate solvent.
[0093] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether with 3 to 10 carbon atoms and a cyclic ether with 3 to 6 carbon atoms. The cyclic ether may be, but not limited to, at least one of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may be, but not limited to, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. The ether compound can be used alone or in any combination and ratio. The amount of the ether compound added is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the high-density lithium-ion battery of the present invention. The volume ratio is usually 1% or more, preferably 2% or more, and more preferably 3% or more in the non-aqueous solvent volume ratio of 100%. In addition, the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less.
[0094] In some embodiments, the nitrile solvent may specifically be but is not limited to at least one of acetonitrile, glutaronitrile, and malononitrile.
[0095] In some embodiments, the carbonate solvent includes a cyclic carbonate or a chain carbonate, and the cyclic carbonate can be specifically but not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), and butylene carbonate (BC); the chain carbonate can be specifically but not limited to at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC). There is no special restriction on the content of the cyclic carbonate, and it is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention, but when one is used alone, the lower limit of its content is usually 3% or more by volume, preferably 5% or more by volume, relative to the total amount of solvent in the non-aqueous electrolyte. By setting this range, the reduction in conductivity due to the reduction in the dielectric constant of the non-aqueous electrolyte can be avoided, and it is easy to make the large current discharge characteristics, stability relative to the negative electrode, and cycle characteristics of the non-aqueous electrolyte battery reach a good range. In addition, the upper limit is usually less than 90% by volume, preferably less than 85% by volume, and more preferably less than 80% by volume. By setting this range, the oxidation / reduction tolerance of the nonaqueous electrolyte can be improved, thereby helping to improve the stability during high temperature storage. The content of the linear carbonate is not particularly limited, and relative to the total amount of solvent of the nonaqueous electrolyte, it is usually more than 15% by volume, preferably more than 20% by volume, and more preferably more than 25% by volume. In addition, usually the volume ratio is less than 90%, preferably less than 85% by volume, and more preferably less than 80% by volume. By making the content of the linear carbonate in the above-mentioned range, it is easy to make the viscosity of the nonaqueous electrolyte reach an appropriate range, suppress the reduction of ionic conductivity, and then help to make the output characteristics of the nonaqueous electrolyte battery reach a good range. When two or more linear carbonates are used in combination, the total amount of the linear carbonate is made to meet the above-mentioned range.
[0096] In certain embodiments, it is also possible to preferably use chain carbonates with fluorine atoms (hereinafter referred to as "fluorinated chain carbonates"). The number of fluorine atoms possessed by the fluorinated chain carbonate is not particularly limited as long as it is more than 1, but is generally less than 6, preferably less than 4. When the fluorinated chain carbonate has a plurality of fluorine atoms, these fluorine atoms can be bonded to the same carbon or to different carbons. As the fluorinated chain carbonate, fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, fluorinated diethyl carbonate derivatives, etc. can be listed.
[0097] Carboxylate solvents include cyclic carboxylate and / or chain carbonate. Examples of cyclic carboxylate include at least one of γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Examples of chain carbonate include at least one of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), and butyl propionate.
[0098] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. There is no special restriction on the amount of sulfone solvent added, and it is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. Relative to the total amount of solvent in the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of sulfone solvents can meet the above range. When the amount of sulfone solvent added is within the above range, a non-aqueous electrolyte with excellent high temperature storage stability tends to be obtained.
[0099] In a preferred embodiment, the non-aqueous organic solvent is a mixture of cyclic carbonate and chain carbonate.
[0100] Another embodiment of the present invention provides a battery, comprising a positive electrode, a negative electrode, and the non-aqueous electrolyte as described above.
[0101] In a specific embodiment, the secondary battery is a lithium metal battery, a lithium ion battery, a lithium sulfur battery, a sodium ion battery, a magnesium ion battery, etc.
[0102] In some embodiments, the positive electrode includes a positive electrode material layer, and the positive electrode material layer includes a positive electrode active material. The type and content of the positive electrode active material are not particularly limited and can be selected according to actual needs, as long as it is a positive electrode active material or a conversion positive electrode material that can reversibly embed / de-embed metal ions (lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, aluminum ions, etc.).
[0103] In a preferred embodiment, the secondary battery is a lithium-ion battery, and its positive electrode active material can be selected from LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-zO2, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1, and the positive electrode active material can also be selected from at least one of sulfide, selenide and halide. More preferably, the positive electrode active material can be selected from LiCoO2, LiFePO4, LiFe 0.8 Mn 0.2 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2、LiNi 0.5 Co 0.2 Al 0.3 At least one of O2.
[0104] In a preferred embodiment, the secondary battery is a sodium ion battery, and its positive electrode active material includes but is not limited to at least one of transition metal oxides, Prussian materials, phosphates, sulfates, and titanate materials. The chemical formula of the transition metal oxide can be Na z M x O y , M can be selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V. More preferably, the transition metal oxide is NaNi m Fe n Mn p O2(m+n+p=1,0≤m≤1,0≤n≤1,0≤p≤1) or NaNi m Co n Mn p O2 (m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1); the molecular formula of the Prussian material is Na x M[M′(CN)6] y·zH2O, where M is a transition metal, M' is a transition metal, 0 < x ≤ 2, 0.8 ≤ y < 1, 0 < z ≤ 20. More preferably, the Prussian material is Na x Mn[Fe(CN)6] y ·nH2O (0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 10) or Na x Fe[Fe(CN)6] y ·nH2O (0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 10); the chemical formula of the phosphate is Na3(MO 1-x PO4)2F 1+2x , 0 ≤ x ≤ 1, M is selected from at least one of Al, V, Ge, Fe, Ga. More preferably, the phosphate is Na3(VPO4)2F3 or Na3(VOPO4)2F; the chemical formula of the phosphate is Na2MPO4F, M is selected from at least one of Fe, Mn. More preferably, the phosphate is Na2FePO4F or Na2MnPO4F; the titanate material can be selected from at least one of Na2Ti3O7, Na2Ti6O 13 , Na4Ti5O 12 , Li4Ti5O 12 , NaTi2(PO4)3; the chemical formula of the sulfate is Na2M(SO4)2·2H2O, M can be selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V
[0105] In some embodiments, the positive electrode further includes a positive electrode current collector, and the positive electrode material layer is disposed on the surface of the positive electrode current collector.
[0106] The positive electrode current collector is selected from metal materials that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0107] In some embodiments, the positive electrode active material layer further includes a positive electrode binder and a positive electrode conductive agent, and the positive electrode active material, the positive electrode binder, and the positive electrode conductive agent are blended to obtain the positive electrode material layer.
[0108] The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0109] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0110] In some embodiments, the negative electrode includes a negative electrode material layer, and the negative electrode material layer includes a negative electrode active material. The type and content of the negative electrode active material are not particularly limited and can be selected according to actual needs.
[0111] In a preferred embodiment, the secondary battery is a lithium-ion battery, and its negative electrode active material includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials; the tin-based negative electrode may include tin, tin-carbon, tin-oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium-silicon alloy, a lithium-sodium alloy, a lithium-potassium alloy, a lithium-aluminum alloy, a lithium-tin alloy, and a lithium-indium alloy.
[0112] In a preferred embodiment, the secondary battery is a sodium ion battery, and its negative electrode active material includes at least one of metallic sodium, graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloy materials with sodium. Among them, the alloy material can also be selected from an alloy material composed of at least one of Si, Ge, Sn, Pb, Sb and C, the graphite can be selected from at least one of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys.
[0113] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer is disposed on the surface of the negative electrode current collector. The material of the negative electrode current collector may be the same as that of the positive electrode current collector, which will not be described in detail herein.
[0114] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are mixed to obtain the negative electrode material layer. The negative electrode binder and the negative electrode conductive agent may be the same as the positive electrode binder and the positive electrode conductive agent, respectively, and will not be described in detail here.
[0115] In some embodiments, the secondary battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.
[0116] The diaphragm may be an existing conventional diaphragm, which may be a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0117] The present invention is further described below by way of examples.
[0118] Table 1
[0119]
[0120] Note: The compounds used in the following examples and comparative examples are selected from Table 1.
[0121] Examples 1 to 16
[0122] Examples 1 to 16 are used to illustrate the non-aqueous electrolyte, lithium ion battery and preparation method thereof disclosed in the present invention, and include the following steps:
[0123] 1) Preparation of non-aqueous electrolyte:
[0124] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of EC:DEC:EMC=1:1:1, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1.05 mol / L. Additives are added based on the total weight of the non-aqueous electrolyte as 100%. The types and contents of the additives are shown in Tables 2 and 3.
[0125] 2) Preparation of positive electrode sheet:
[0126] The positive electrode active material lithium nickel cobalt manganese oxide LiNi was mixed in a mass ratio of 93:4:3 0.5 Co 0.2 Mn 0.3O2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF), and then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with aluminum lead wires using an ultrasonic welder to obtain a positive electrode sheet with a thickness of between 120-150μm.
[0127] 3) Preparation of negative electrode sheet:
[0128] The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain a negative electrode slurry. The slurry is coated on both sides of the copper foil, dried, rolled and vacuum dried, and a nickel lead wire is welded with an ultrasonic welder to obtain a negative electrode plate with a thickness of 120-150μm.
[0129] 4) Preparation of battery cells:
[0130] A three-layer separator with a thickness of 20 μm was placed between the positive electrode plate and the negative electrode plate, and then the sandwich structure consisting of the positive electrode sheet, the negative electrode sheet and the separator was wound. The wound body was flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid.
[0131] 5) Battery filling and formation:
[0132] In a glove box with a dew point controlled below -40°C, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left to stand for 24 hours.
[0133] Then, the conventional formation of the first charge was carried out according to the following steps: 0.05C constant current charging for 180min, 0.2C constant current charging to 3.95V, secondary vacuum sealing, and then further 0.2C constant current charging to 4.2V, after being placed at room temperature for 24h, 0.2C constant current discharge to 3.0V, a LiNi 0.5 Co 0.2 Mn 0.3 O2 / artificial graphite lithium-ion battery.
[0134] Comparative Examples 1 to 4
[0135] Comparative Examples 1 to 4 are used to compare and illustrate the non-aqueous electrolyte, lithium ion battery and preparation method thereof disclosed in the present invention, and include most of the operation steps in Example 1, except that:
[0136] The types and contents of additives in the non-aqueous electrolyte are shown in Tables 2 and 3.
[0137] Performance Testing
[0138] The lithium-ion battery prepared above was subjected to the following performance tests:
[0139] High temperature storage performance test
[0140] The formed lithium-ion battery is charged to 4.2V at a constant current of 1C at room temperature, then charged at a constant current and constant voltage until the current drops to 0.05C, and then discharged to 3.0V at a constant current of 1C, and the initial discharge capacity D1, initial battery volume V1 and initial impedance F1 of the battery are measured. After charging to full capacity and storing in a 60°C environment for 30 days, it is discharged to 3V at 1C, and the battery retention capacity D2, recovery capacity D3, impedance F2 after storage and battery volume V2 after storage are measured. The calculation formula is as follows:
[0141] Battery capacity retention rate (%) = retention capacity D2 / initial capacity D1×100%;
[0142] Battery capacity recovery rate (%) = recovery capacity D3 / initial capacity D1×100%;
[0143] Volume expansion rate (%) = (battery volume after storage V2-initial battery volume V1) / initial battery volume V1×100%;
[0144] Internal resistance growth rate (%) = (post-storage impedance F2 - initial impedance F1) / initial impedance F1 × 100%.
[0145] 1. Fill in the test results obtained in Examples 1 to 11 and Comparative Examples 1 to 4 into Table 2.
[0146] Table 2
[0147]
[0148]
[0149] It can be seen from the test results of Examples 1 to 8 and Comparative Example 1 that, compared with a non-aqueous electrolyte without adding the compound of Structural Formula 1, adding the compound of Structural Formula 1 as an additive in the non-aqueous electrolyte can effectively improve the high temperature performance of the lithium ion battery. From the test results of Examples 1-8, it can be seen that as the content of the compound of Structural Formula 1 increases, the high temperature storage performance of the lithium ion battery first increases and then decreases, especially when the content of the compound is 0.5%-5.0%, the lithium ion battery has the best comprehensive performance, indicating that during the charge and discharge cycle of the lithium ion battery, when the content of the compound of Structural Formula 1 in the electrolyte is 0.5%-5.0%, it can ensure that the formed SEI film is regular and of moderate thickness, and has better stability.
[0150] From the comparison of the test results of Example 4 and Comparative Examples 2-4, it can be seen that compared with traditional vinylene carbonate (VC), vinyl sulfate (DTD) and 1,3-propane sultone (PS), the use of the compound represented by structural formula 1 provided in the present application as an additive can more significantly improve the storage performance of lithium-ion batteries at high temperatures, indicating that the passivation film formed by the compound represented by structural formula 1 has better high-temperature stability and is not easily destroyed under high temperature conditions.
[0151] It can be seen from the test results of Examples 4 and 9 to 11 that the use of vinylene carbonate (VC), vinyl sulfate (DTD) or 1,3-propane sultone (PS) in combination with the compound shown in Structural Formula 1 can more significantly improve the high-temperature storage performance of lithium-ion batteries. It is speculated that this is because VC, DTD, PS and the compound shown in Structural Formula 1 jointly participate in the formation of the passivation film on the surface of the positive and negative electrodes, which is beneficial to improving the quality of the passivation film.
[0152] 2. Fill in Table 3 with the test results obtained in Examples 4, 12 to 16 and Comparative Examples 1 to 4.
[0153] Table 3
[0154]
[0155]
[0156] By comparing the test results of Examples 4, 12 to 16 and Comparative Examples 1 to 4, it can be seen that compared with lithium ion batteries without additives or with existing additives, the lithium ion batteries obtained by using the compound of structural formula I provided by the present invention as an additive have better high-temperature storage performance.
[0157] Examples 17 to 32
[0158] Examples 17 to 32 are used to illustrate the preparation method of the non-aqueous electrolyte and the sodium ion battery disclosed in the present invention, and include the following steps:
[0159] 1) Preparation of non-aqueous electrolyte:
[0160] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of EC:DEC:EMC=1:1:1, and then sodium hexafluorophosphate (NaPF6) is added to a molar concentration of 1.05 mol / L. Additives are added based on the total weight of the non-aqueous electrolyte as 100%. The types and contents of the additives are shown in Tables 4 and 5.
[0161] 2) Preparation of positive electrode sheet:
[0162] The positive electrode active material Na3V2(PO4)3, the conductive carbon black Super-P and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 94:3:3, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with aluminum or nickel lead wires using an ultrasonic welder to obtain a positive electrode sheet with a thickness of 80-200μm.
[0163] 3) Preparation of negative electrode sheet:
[0164] The negative electrode active material spherical hard carbon, conductive carbon black Super-P, binder styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 97:1:1:1, and then dispersed in deionized water to obtain a negative electrode slurry. The slurry is coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with aluminum or nickel lead wires using an ultrasonic welder to obtain a negative electrode sheet with a thickness between 80-300μm.
[0165] 4) The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, and the preparation of the sodium ion battery is completed by aluminum-plastic film packaging, re-baking, liquid injection, static placement, formation, fixture shaping, secondary sealing, and capacity testing.
[0166] Comparative Examples 5 to 8
[0167] Comparative Examples 5 to 8 are used to compare and illustrate the preparation methods of the non-aqueous electrolyte and the sodium ion battery disclosed in the present invention, and include most of the operating steps in Example 17, except that:
[0168] The types and contents of additives in the non-aqueous electrolyte are shown in Tables 4 and 5.
[0169] Performance Testing
[0170] The sodium ion batteries prepared in the examples and comparative examples were subjected to the following performance tests:
[0171] High temperature storage performance test
[0172] The formed sodium ion battery was charged to 4.0V at a constant current of 0.5C at room temperature, then charged at a constant voltage until the current dropped to 0.03C, and then discharged to 1.5V at a constant current of 1C, and the initial discharge capacity D1, initial battery volume V1 and initial impedance F1 of the battery were measured. After being fully charged and stored at 60°C for 30 days, it was discharged to 3V at 1C, and the battery retention capacity D2, recovery capacity D3, impedance F2 after storage and battery volume V2 after storage were measured. The calculation formula is as follows:
[0173] Battery capacity retention rate (%) = retention capacity D2 / initial capacity D1×100%;
[0174] Battery capacity recovery rate (%) = recovery capacity D3 / initial capacity D1×100%;
[0175] Volume expansion rate (%) = (battery volume after storage V2-initial battery volume V1) / initial battery volume V1×100%;
[0176] Internal resistance growth rate (%) = (post-storage impedance F2 - initial impedance F1) / initial impedance F1 × 100%.
[0177] 3. Fill in Table 4 with the test results obtained from Examples 17 to 27 and Comparative Examples 5 to 8.
[0178] Table 4
[0179]
[0180]
[0181] Comparing the test results of Examples 17-27 and Comparative Examples 5-8, it can be seen that, similar to the role played by the compound shown in Structural Formula 1 in lithium-ion batteries, adding the compound shown in Structural Formula 1 to the non-aqueous electrolyte of sodium-ion batteries can also improve the high-temperature storage performance of sodium-ion batteries, indicating that the passivation film formed by the decomposition of the compound shown in Structural Formula 1 on the surface of the positive and negative electrodes has a high high-temperature stability, improves the performance stability of the positive and negative electrode materials in long-term cycles, and improves the cycle performance and storage performance of sodium-ion batteries at high temperatures. From the test results of Examples 17-27, it can be seen that as the content of the compound shown in Structural Formula 1 increases, the high-temperature storage performance and high-temperature cycle performance of the sodium-ion battery first increase and then decrease, especially when the content of the compound is 0.1% to 2%, the sodium-ion battery has the best comprehensive performance, indicating that during the charge and discharge cycle of the sodium-ion battery, when the content of the compound shown in Structural Formula 1 in the electrolyte is 0.5% to 5%, it can ensure that the formed SEI film is regular and of moderate thickness, and has better stability.
[0182] It can be seen from the test results of Example 20 and Comparative Examples 5-8 that, compared with conventional film-forming additives, such as vinylene carbonate (VC), vinyl sulfate (DTD) or fluoroethylene carbonate (FEC), the use of the compound represented by structural formula 1 provided in the present application as an additive can more significantly improve the storage performance of sodium ion batteries at high temperatures, and the passivation film formed by the compound represented by structural formula 1 has better high temperature stability.
[0183] It can be seen from the test results of Examples 20, 25 to 27 that the use of vinylene carbonate (VC), vinyl sulfate (DTD) or fluoroethylene carbonate (FEC) in combination with the compound shown in Structural Formula 1 can more significantly improve the high temperature cycle performance of the sodium ion battery. It is speculated that this is because VC, DTD or FEC and the compound shown in Structural Formula 1 jointly participate in the formation of the passivation film on the surface of the positive and negative electrodes, which is beneficial to improving the quality of the passivation film.
[0184] 4. Fill in Table 5 with the test results obtained in Examples 20, 28 to 32 and Comparative Examples 5 to 8.
[0185] Table 5
[0186]
[0187]
[0188] From the test results of Comparative Examples 20, 28 to 32 and Comparative Examples 5 to 8, it can be seen that compared with sodium ion batteries without additives or with existing additives, the sodium ion batteries obtained by using the compound of structural formula I provided by the present invention as an additive have better high temperature cycle performance.
[0189] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A compound, characterized in that Selected from the compounds shown in structural formula 1: wherein x is an integer of 0-3, y is an integer of 0-3, 1≤x+y, a is an integer of 0-4, b is an integer of 0-4, c is an integer of 0-4, 1≤a+b+c, R1, R2 and R3 are each independently selected from an alkylene group having 1-4 carbon atoms, R4 and R5 are each independently selected from hydrogen or an alkyl group having 1-6 carbon atoms; R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 and R 14 Each is independently selected from an alkyl group having 1 to 6 carbon atoms.
2. The compound according to claim 1, characterized in that x+y≤3, a+b+c≤8.
3. The compound according to claim 1, characterized in that The compound represented by the structural formula 1 is selected from one or more of the following compounds:
4. Use of the compound according to any one of claims 1 to 3 as an additive for non-aqueous electrolyte.
5. A non-aqueous electrolyte, characterized in that: The invention comprises a non-aqueous organic solvent, an electrolyte salt and a first additive, wherein the first additive comprises the compound according to any one of claims 1 to 3.
6. The non-aqueous electrolyte according to claim 5, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the content of the compound represented by the structural formula 1 is 0.05-10%.
7. The non-aqueous electrolyte according to claim 5, characterized in that The electrolyte salt is selected from at least one of lithium salts, sodium salts, potassium salts, magnesium salts, zinc salts and aluminum salts.
8. The non-aqueous electrolyte according to claim 5, characterized in that The non-aqueous electrolyte further includes a second additive, and the second additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a borate compound, and a nitrile compound.
9. The non-aqueous electrolyte according to claim 8, characterized in that The cyclic sulfate ester compound is selected from vinyl sulfate, 4-methylvinyl sulfate, propylene sulfate, At least one of; The sultone compound is selected from 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, At least one of; The cyclic carbonate compound is selected from at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate or the compound shown in Structural Formula 2: In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group; The phosphate compound is selected from at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in structural formula 3: In the structural formula 3, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , R 33 At least one of them is an unsaturated hydrocarbon group; The borate compound is selected from at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate; The nitrile compound is selected from at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
10. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the non-aqueous electrolyte as claimed in any one of claims 5 to 9.